Young Adult Ministry: Dogma, Spirituality, and Stages of Faith - Mullen, Timothy (Journal for the academic study of religion, 2023)
The research reported in this article examines what can be learnt from listening to young people who stay engaged with churches and those who leave. This research compared both groups' experiences for further analysis. The authors analysed fourteen qualitative phenomenological interviews with young people aged 19-28 that documented young adults' experiences of the Baptist Church in Perth, Western Australia. Attitudes to spirituality and dogma were central themes relevant to young people's decision-making. The data was then compared with Fowler's faith development theory, to find that many of the participants displayed faith styles reminiscent of individuative reflective faith, and their communities exhibited modal development akin to synthetic-conventional and mythic-literal faith. The article concludes by suggesting that young people (both those who stayed and those who left the church) were seeking dialogue about faith and spirituality, and that dissonance between young people's faith style and the modal faith style of their church community affected decisions to stay or leave the church, and this relationship was not always straightforward. The implications for youth ministry are that it would be beneficial to focus more on dialogue about faith which accommodates and explores disagreement and less on dogma.